Adopting Dialectical Leadership Behavior on improving Transformational Entrepreneurship Analytical Research at the Ministry of Foreign Affairs (Journal of Accounting and Financial Studies ( JAFS ), 2026)
The current research aims to understand ability of Iraqi Ministry of Foreign Affairs to adopt Dialectical Leadership Behavior across its dimensions (Timely Adaptation, Individual Guidance, Balancing Kindness and Strictness, Balancing Contradictions, Enhancing Coordination, and Comprehensive Management) to improve Transformational Entrepreneurship across its dimensions (Quality of Human Capital, Embracing Risk and Seizing Opportunities, and Assessing Changing Situation). Given that transformational Entrepreneurial ship is a greater societal demand that increases well-being of Iraqi society, and ministry’s unique ability to coordinate ambitions and goals with relationships it can achieve, which brings it greater returns and benefits, descriptive-analytical approach, based on a quantitative and qualitative perspective, covers the requirements for a comprehensive understanding of a variables under study. It relied on a survey of opinions from a sample of (110) job titles (First Secretary, Second Secretary, Third Secretary), as they are most likely to understand a dialectical behavior of their leadership. Furthermore, they are middle-level leaders who alternate between working between a ministry's headquarters and Iraqi embassies as employees in the diplomatic corps, they represent (94.5%) of the community, which numbers (154) individuals, The survey was conducted on basis of a questionnaire. Prepared from solid foreign standards, the opinions of experts and evaluators from various Iraqi and Arab universities were added. A statistical package (SPSS V.28) was adopted, after adopting a number of important statistical tests employed to verify the main hypothesis in calculating: Mean, Standard Deviation, relative Importance, and Coefficient of Variation, research then resorted to multiple linear regression tests to determine most prominent practical outcome of Ministry of Foreign Affairs' direct adoption of Dialectical Leadership to improve its transformational Entrepreneurship.  Ministry was able to adopt (timely adaptation, balancing kindness and rigor, balancing contradictions, enhancing coordination, and comprehensive management) to improve transformational leadership. Some practices were found to have fallen short of sample’s aspirations and to have weakened a dimension investigated in practice, as the Ministry sought to adopt both variables in terms of application and attention.